?EFFECTS OF PROBE SHAPES ON THE BARRIER HEIGHT AND SURFACE CONDUCTANCE OF TELLURIUM THIN FILMS (Biological Sciences - PJSIR, 1999)
The study centered on the effects of probe shapes on the conductance and barrier height of Tellurium thin films. It was found that the shape of the contacts affected the conducting behaviour of the films. The conductances of each of the sample used changed with the shape of the contacts. This can even bediscovered with those of the differential electrodes having relatively lower conductance compared with their counterparts. However, the study revealed that the shape of the contacts had no significant effects on the barrier height of tellurium thin films.